Domibacillus mangrovi sp nov and domibacillus epiphyticus sp nov., isolated from marine habitats of the central west coast of India - Verma, Ashish; Ojha, Anup Kumar; Dastager, Syed G.; Natarajan, Rameshkumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (International Journal of Systematic and Evolutionary Microbiology, 2017)
While studying culturable bacterial diversity in different marine habitats of the central west coast of India, two novel Gramstain-positive, strictly aerobic, motile, endospore-forming and rod-shaped bacterial strains designated as SAOS 44(T) and SAB 38(T) were isolated from mangrove sediment soil and the surface of a macroalga, respectively. The strains were taxonomically characterized by using a polyphasic approach and genomic methods. The phylogenetic analysis based on 16S rRNA gene sequencing placed the strains firmly in the genus Domibacillus and were most closely related to Domibacillus antri KCTC 33636(T). The predominant fatty acids were iso-C-15 : 0 and anteiso-C-15 : 0. The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol in addition to an aminophosphoglycolipid. MK-6 was the only respiratory quinone. The range of values of digital DNA-DNA hybridization (19.2-24.9 %) and the ortho-average nucleotide identity (74.1-81.4 %) among strains SAOS 44(T), SAB 38(T) and other Domibacillus species clearly supports their status as a distinct and novel species for which the names Domibacillus mangrovi sp. nov. SAOS 44(T) (=DSM 100930(T)=KCTC 33820(T)=MTCC 12571(T)) and Domibacillus epiphyticus sp. nov. SAB 38(T) (=DSM 100929(T)= KCTC 33830(T)=MTCC 12575(T)) are proposed, respectively.